The Influence of Internal and External Factors on the Stock Returns of Idx30 for the 2019-2023 Period - Prameswari, Rania; Sakti, Rachmad Kresna (Contemporary Studies in Economic, Finance and Banking, 2026)
Climate change, sustainability demands, and global economic instability encourage investors to consider internal and external aspects in investment decisions. This study aims to analyze the influence of internal factors including Environment, Social, Governance performance through ESG Score, net income, ROA, EPS, and DPS, as well as external factors in the form of inflation, BI rate, and economic growth on the stock returns of companies incorporated in the IDX30 index for the 2019-2023 period. This research uses a quantitative approach with the panel data regression method. The data used is obtained from company financial reports, sustainability reports, and official macroeconomic data. Stock returns are calculated based on annual capital gains. The statistical test results show that Environment score, inflation, BI rate, Price Earning Ratio, and net income have a significant influence on stock returns, while Social and Governance score, ROA, EPS, DPS, and economic growth are not partially significant, but simultaneously significant. . These findings suggest that environmental sustainability factors, financial performance, and macroeconomic conditions need to be the main considerations in investment strategies in the Indonesian stock market. This research is expected to contribute to investors, issuers, regulators, and academics in understanding the dynamics of the stock market under current economic conditions.